Interventional Study for Improving Health Information System in Khyber Pakhtunkhwa, Pakistan - Nawaz, Rab (Cureus, 2020)
Objective To assess the improvement in the health information system in the district Nowshera by integrating the data reporting of the Expanded Program on Immunization (EPI) and Lady Health Worker (LHW) programs in the existing system. Methodology The study was conducted at district Nowshera and Swabi, Pakistan between May 2015 and May 2016 for a duration of one year. The data collection instruments used in the study were adapted from the Performance of Routine Information System Management (PRISM) tool package. The study was conducted in three phases during a period of one year. The first three months were utilized for baseline assessment. The next six months were being used for implementing the integration of the EPI and LHW, and the next three months were being used for the post-intervention evaluation. Microsoft Excel software was used to enter and analyze the data. A p < 0.05 was considered as the cut-off value for significance. Results The results indicated that the integration of data from the EPI and LHW with that of the existing Health Information System (HIS) is possible and has the potential for improving the existing system. The least significant results were produced by the use of information, which depicts that the utilization of data in decision making or policy making is still needed to be improved. Moreover, we reported a lack of enforcement and regulation by the authorities in monitoring the feedback system in the HIS. Conclusion The current study revealed significant improvements in the use of information, data quality, and behavior of staff. It is essential to properly train the team on how to operate the District Health Information System (DHIS) to gain adequate and timely data on health status and determinants. Additionally, the integration would benefit in managing the data at not only the national level but at the district level too.